2019
DOI: 10.1016/j.heares.2019.02.016
|View full text |Cite
|
Sign up to set email alerts
|

The search for noise-induced cochlear synaptopathy in humans: Mission impossible?

Abstract: Animal studies demonstrate that noise exposure can permanently damage the synapses between inner hair cells and auditory nerve fibers, even when outer hair cells are intact and there is no clinically relevant permanent threshold shift. Synaptopathy disrupts the afferent connection between the cochlea and the central auditory system and is predicted to impair speech understanding in noisy environments and potentially result in tinnitus and/or hyperacusis. While cochlear synaptopathy has been demonstrated in num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
136
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(142 citation statements)
references
References 108 publications
3
136
2
1
Order By: Relevance
“…Following a similar approach, noise exposure history did not relate to the ABR Wave-I amplitude, or EFR measures, in young adults with and without tinnitus (Fulbright et al, 2017;Guest et al, 2017), or in 100 participants with normal audiometric thresholds (Prendergast et al, 2017). From the listed studies, we can either conclude that noiseinduced cochlear synaptopathy might not play an important role in young adults with normal audiometric hearing thresholds, or that the adopted electrophysiological measures are not sensitive enough to reveal subtle differences in neural fibre populations in this particular group (see Bramhall et al (2019) for an overview).…”
Section: Introductionmentioning
confidence: 95%
“…Following a similar approach, noise exposure history did not relate to the ABR Wave-I amplitude, or EFR measures, in young adults with and without tinnitus (Fulbright et al, 2017;Guest et al, 2017), or in 100 participants with normal audiometric thresholds (Prendergast et al, 2017). From the listed studies, we can either conclude that noiseinduced cochlear synaptopathy might not play an important role in young adults with normal audiometric hearing thresholds, or that the adopted electrophysiological measures are not sensitive enough to reveal subtle differences in neural fibre populations in this particular group (see Bramhall et al (2019) for an overview).…”
Section: Introductionmentioning
confidence: 95%
“…However, a direct translation of animal-based AEP metrics to human synaptopathy diagnostics has proven difficult because a direct quantification of synaptopathy is only possible via histology and hence impossible in living humans. Secondly, inter-individual differences in neural backgroundnoise level, sex and head size (Trune et al, 1988;Mitchell et al, 1989;Hickox et al, 2017) can confound the interpretation of AEP amplitudes in terms of hearing status and require differential AEP metrics (e.g., Bharadwaj et al, 2015;Verhulst et al, 2016;Guest et al, 2018;Bramhall et al, 2019). Lastly, AEP metrics are not only compromised by synaptopathy, OHC damage is also known to affect the AEP (e.g., Gorga et al, 1985;Herdman and Stapells, 2003;Chen et al, 2007;Garrett and Verhulst, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…16 In a recent systematic review, findings pro and against the cochlea synaptopathy hypothesis were controversial. 17 Liberman et al identified significant differences in AP/AP ratio in electrocochleography between two groups of young adults with and without history of noise exposure. Bramhall et al also identified difference in ABR wave I amplitude between veterans with and without exposure to gunshots.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies used history of noise exposure, either for the whole life time or during the past 12 months before measurements. 17 Several studies, concluded that wave I was significantly reduced in groups with increased noise exposure, whereas others did not. 18.21-23,25-27 However, most of these studies suffered from methodological flaws and diversities, including variance in measurement and settings, reduced synaptic vulnerability in humans compared to animals, limited range of exposure thresholds inducing either detectable or clinically apparent synaptopathy, existence of synaptopathy in normal population (and thus inability to detect differences) and confounding effect of co-existing OHC functional insufficiencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation